Synthesis and characterisation of a new benzamide-containing nitrobenzoxadiazole as a GSTP1-1 inhibitor endowed with high stability to metabolic hydrolysis. (1st January 2019) - Di Paolo, Veronica; Fulci, Chiara; Rotili, Dante; Sciarretta, Francesca; Lucidi, Alessia; Morozzo della Rocca, Blasco; De Luca, Anastasia; Rosato, Antonio; Quintieri, Luigi; Caccuri, Anna Maria
Abstract: The antitumor agent 6-((7-nitrobenzo[ c ][1, 2, 5]oxadiazol-4-yl)thio)hexan-1-ol (1 ) is a potent inhibitor of GSTP1-1, a glutathione S -transferase capable of inhibiting apoptosis by binding to JNK1 and TRAF2. We recently demonstrated that, unlike its parent compound, the benzoyl ester of 1 (compound 3 ) exhibits negligible reactivity towards GSH, and has a different mode of interaction with GSTP1-1. Unfortunately, 3 is susceptible to rapid metabolic hydrolysis. In an effort to improve the metabolic stability of 3, its ester group has been replaced by an amide, leading to N -(6-((7-nitrobenzo[ c ][1, 2, 5]oxadiazol-4-yl)thio)hexyl)benzamide (4 ). Unlike 3, compound 4 was stable to human liver microsomal carboxylesterases, but retained the ability to disrupt the interaction between GSTP1-1 and TRAF2 regardless of GSH levels. Moreover, 4 exhibited both a higher stability in the presence of GSH and a greater cytotoxicity towards cultured A375 melanoma cells, in comparison with 1 and its analog 2 . These findings suggest that 4 deserves further preclinical testing.